Kebijakan Luar Negeri Indonesia Terhadap Mesir Pasca Pemerintahan Husni Mubarak - Deasy Silvya Sari (Indonesia Center for Middle East Studies, 2018)
The article explains the change and continuity of Indonesian Foreign Policy toward Egypt post Husni Mubarak Administration. This issue is explored because after the administration of Husni Mubarak, Egypt experienced domestic political instability in the form of a government regime change in a short time, namely the election of Mursi as president through elections in 2011, the overthrow of Mursi, and the election of Al Sisi as new president in 2013 through elections. This article concludes that on facing some changes in Egypt post-Husni Mubarak, Indonesia did ‘the change and continuity’ in her foreign policy. The ‘change’ was done because of administration of Presiden Yudhoyono wanted to ensure the implementation of Indonesia's national interests, namely, the security of Indonesian citizens in Egypt, education programs, and the sustainability of Indonesia-Egypt trade relations. This change was motivated by bureaucratic advocacy and restructuring domestic agent on decision making of Indonesian government. The ‘continuity’ takes place in terms of Indonesia’s doctrine of foreign policy, namely ‘free and active policy’. 'Free policy’ was carried out impartially in the Egyptian conflict and ‘active policy’ was implemented by maintaining security, education, and trade cooperation with Egypt.